2020
DOI: 10.1002/bjs5.50335
|View full text |Cite
|
Sign up to set email alerts
|

Obese patients and robotic colorectal surgery: systematic review and meta-analysis

Abstract: Background: Obesity is a major health problem, demonstrated to double the risk of colorectal cancer. The benefits of robotic colorectal surgery in obese patients remain largely unknown. This meta-analysis evaluated the clinical and pathological outcomes of robotic colorectal surgery in obese and non-obese patients. Methods: MEDLINE, Embase, Global Health, Healthcare Management Information Consortium (HMIC) and Midwives Information and Resources Service (MIDIRS) databases were searched on 1 August 2018 with no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Focusing on oncologic colorectal surgery, a more recent meta‐analysis of 13 observational studies (4550 patients) reported significant increased conversion rate (OR: 2.11; 1.58–2.81), postoperative morbidity (OR: 1.54; 1.21–1.97), wound infection (OR: 2.43; 1.46–4.03), and anastomotic leak (OR: 1.65; 1.01–2.71) in the obese group 82 . On the contrary to what has been described for other cancers, 82–84 the rate of positive margin (distal and circumferential), 5‐year disease‐free and overall survival, 82 do not convincingly differ between normal‐weight and patients with obesity after laparoscopic, 82 or robotic, 84 surgery.…”
Section: Obesity and Colorectal Cancermentioning
confidence: 81%
“…Focusing on oncologic colorectal surgery, a more recent meta‐analysis of 13 observational studies (4550 patients) reported significant increased conversion rate (OR: 2.11; 1.58–2.81), postoperative morbidity (OR: 1.54; 1.21–1.97), wound infection (OR: 2.43; 1.46–4.03), and anastomotic leak (OR: 1.65; 1.01–2.71) in the obese group 82 . On the contrary to what has been described for other cancers, 82–84 the rate of positive margin (distal and circumferential), 5‐year disease‐free and overall survival, 82 do not convincingly differ between normal‐weight and patients with obesity after laparoscopic, 82 or robotic, 84 surgery.…”
Section: Obesity and Colorectal Cancermentioning
confidence: 81%
“…There were no other significant differences in intra-or post-operative outcomes. The second meta-analysis performed by Suwa et al 28 found a significantly increased operative time and rate of conversion to laparotomy in OB patients. However, given the differences in pathology, surgical treatment, and multimodal treatment between rectal and colon cancer, 29 it is important to investigate colon cancer as a separate disease process.…”
Section: Discussionmentioning
confidence: 98%
“…There were no other significant differences in intra‐ or post‐operative outcomes. The second meta‐analysis performed by Suwa et al 28 . found a significantly increased operative time and rate of conversion to laparotomy in OB patients.…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that obese patients pose a greater technical challenge for minimally invasive colorectal surgery as they tend to have a thicker mesentery and larger omentum, which can result in impaired vision, restricted space for instruments to manoeuvre, distorted surgical planes and troublesome bleeding [17,18]. For these reasons, the RRH cohort likely posed a greater technical challenge than the less obese LRH cohort, which may have contributed to the longer operating time in patients managed by robotic surgery [18][19][20]. However, it is interesting to note that, despite the potential greater technical challenge posed by those undergoing RRH, the well-recognised higher complication rate associated with obese patients was not observed, with equivalent post-operative outcomes to those that underwent LRH.…”
Section: Discussionmentioning
confidence: 99%